Transformasi Pengembangan Kapasitas Guru: Dari Cascade Model ke Pelatihan Berbasis Sekolah di Kota Ambon - Ilyas, Ince Mulyadi; Suatrat, Fatima; Haulussy, Rais Rahman (Populis: Jurnal Ilmu Sosial dan Ilmu Politik, 2023)
Teacher capacity development is a crucial aspect of improving the quality of education, but the model used can affect its effectiveness. This study analyzes the transformation of teacher capacity development in Ambon City from the cascade model approach to school-based training. The cascade model, which has been commonly applied, tends to experience material dilution during the delivery process and fails to fully meet the needs for improving teacher capacity. This model also limits the definition of capacity and its target beneficiaries. To address these limitations, this study proposes an expanded capacity development model, including continuous school-based training for all teachers, incremental training, and regular training for trainers and school principals. The study employs a qualitative approach with data collection techniques through in-depth interviews, observations, and document analysis. The findings show that the school-based approach is more effective in comprehensively improving teacher competence compared to the cascade model. This study contributes to the academic discourse on the best strategies for teacher capacity development in Indonesia, particularly in Ambon City. It also provides valuable insights for stakeholders in similar contexts. Therefore, the policy recommendations from this study can serve as a reference for the development of social sciences and humanities, particularly in designing more inclusive and sustainable education policies.